Nosilnost natezno obremenjenih vijačnih preklopnih spojev s steklenimi vlakni utrjenih ploščatih polimernih kompozitnih elementov - Antolinc, David (Gradbeni vestnik, 2022)
The present article highlights the main technical and design challenges of using fiber reinforced plastics (FRP) composite materials as the main structural material. Connection details between composite FRP elements present a special challenge. Therefore, within the present study, commonly used bolted lap connections assembled of glass fiber reinforced polymer composite GFRP plates, connected with one steel bolt M24, were studied and analyzed. According to the design recommendations from the literature and particularly from the EC standard development guidance for composite FRP structural design for this type of connections, three different distances e between the loaded GFRP plate edge and the center of the bolt hole with diameter d0 were defined. The first distance of the hole centerline e was 1.5d, second 3.5d and the third one at a distance of 7d from the edge of the GFRP plate. The tensile tests were conducted in order to verify the adequacy of the analytical expressions provided in document »Prospect for new guidance in the design of FRP« (Ascione, 2016), which is proposed for the design of bolted lap connections, and the definition of their failure mechanisms. Based on the experimental analysis results, the comments on the design limitations provided in the above mentioned guidelines are given for the considered lap joints. The comparison of the experimental and analytical results shows that the analytical expressions give very conservative results and that these expressions could be optimized.
Keywords: bearing stress; bočni pritisk; bolted connection; composite; failure mechanisms; glass fiber reinforced polymer (GFRP); kompozit; natezno obremenjen vijačeni spoj; nosilnost; porušni mehanizem; s steklenimi vlakni armirana plastika (GFRP); tension load capacity